DEVELOPMENT OF OIL-WATER SEPARATION MODELS INCORPORATING PHYSICAL PROPERTIES AND COALESCENCE PHENOMENA - ALEEM, WAQAS (2018)
Oil-water separation efficiency in the gravity separators affects all the downstream equipment’s performance. Due to the oil well depletion and application of EOR technologies, high amount of water, stable emulsion are being produced and the properties of oil-water are changing that reduces the efficiency of gravity separator.